IPM Approach for the Control of Major Defoliators of Primary Tasar Food Plants - Sharma, S. P.; Kishore, Ram; Sinha, B. R. R. P.; Thangavelu, K. (Indian Forester, 2006)
Defoliators Anomala blanchardi Blanch, Tricliona picea Jacoby, T. variabilis Jac., Myllocerus viridanus Fab. and Notolophus antiqua Linn. are the major pests of primary tasar food plants, namely, Terminalia arjuna Bedd and T. tomentosa W&A causing 15-20% foliage unsuitable for silkworm feeding. The soil application of neem cake (60 kg/acre) and foliar spray of Azadirachtin (6.0 ppm) were found effective in suppressing growth and development of coleopteran grubs and lepidopteran larvae respectively. Based upon these finding, various control measures such as cultural (deep digging of soil), mechanical (collection and destruction of different developmental stages), soil application of neem cake, foliar application of Azadirachtin and combination of these four control measures (IPM) were taken up for evaluation of their efficacy. The averages of leaf yield per plant, leaf damage per cent and number of grubs per cubic feet for each treatment were recorded. Results reveal that IPM was effective (leaf yield/plant-4.266 kg, leaf damage - 11.25% and number of grubs/cft - 0.125) as compared to control (leaf yield/plant - 2.468 kg, leaf damage - 40% and number of grubs/cft. - 1.750) in controlling the defoliators. The foliage damage could be reduced by 71-87% over control by adopting IPM. The safe period for Azadirachtin was found to be 5 days for tasar silkworm, Antheraea mylitta D.